"Reconozca de Dios el cetro": la misión divina del rey en el pensamiento de Saavedra Fajardo = Abweichender Titel: "Let a Prince always Acknowledge his Rule and Scepter from God" : The Divine Mission of the King in the Thought of Saavedra Fajardo - Meer Cañón, Ramón de (Cauriensia, 2025)
Diego de Saavedra Fajardo is a baroque author deeply influenced by a classical worldview and political thought, rooted in the realist Middle Ages, Aristotelian philosophy and Christian doctrine. This is especially relevant as far as his understanding of the relationship between the king, political power, the Church and God is concerned. In this first article, we will examine the type of connection existing in Saavedra's thought between the king and God, his relationship with the sacred, and, most importantly, the type of relationship Saavedra advocates between the temporal sphere and the Church as a spiritual sphere. Defining the autonomy and interdependence between powers will lay the groundwork for a second article on the spiritual function of the king.